Efecto a la aplicación de tres fungicidas para el control de la pudrición blanca (Sclerotinia cepivorum) en el cultivo de cebolla burguesa en el sector la Paz provincia del Carchi - Cuamacas Vallejos, Renán Eduardo (2013)
In the research the onion crop response to the application of chemical, biological, botanical for handling white rot (Sclerotinia cepivoum (production of onion crop in the parish of La Paz county Montufar fungicides evaluated Carchi, High 100 products (chemical) were tested in doses of 400,500 cc / ha; Tricomplex (fungicide) at doses of 200, 250 ml / ha and Kamilforte (chamomile extract at 300 and 400 ml / ha. Were applied to transplantation, 15,23,30 days after the first application. Complete block design with 7 safflower treatments and 3 replications. Incidence and disease severity, plant height, diameter and weight of the buboes .the performance was evaluated results showed that the yield performance of the onion, lower incidence and severity of white rot disease, Tricomplex present at doses of 200 and 250 ml / ha. The best plant height and vigor came with the product application based Kamilforte chamomile extract. Best performance and record net income as applying Tricomplex per 250 cc / ha.